The role of parents as partners in early childhood education in kindergarten Singapore International school Cilegon: a descriptive study - Nadhilah, Annisa; Winarti, Anur; Huzaimah, Dewi; Nisrina, Fatin Adha; Solehah, Ida; Lisnawati, Rani; Hartanto, Revina Julia; Sapriah; Jubaedah, Siti; Mashudi, Esya Anesty (International Conference on Education in Primary and Early Childhood, Marine, Computer Information, and Logistics, 2025)
This study aims to describe the role of parents as partners in early childhood education at TK SIS Cilegon. Parental involvement means that parents are involved in educating their children, both at home and at school. This is because parents are the first people to interact and educate children at home. The method used in this study is descriptive qualitative through observation, interviews and documentation as data collection techniques. The subjects of the study were teachers and parents. The data analysis technique used the Miles and Hubberman model consisting of data reduction, data presentation, and data verification stages. This article will discuss the implementation of the parent involvement program, identification of issues and problems of the parent involvement program, and solutions for developing the parent involvement program at TK SIS Cilegon. The results of the study showed that parents at TK SIS Cilegon played an active role in supporting the child’s education process through good communication with teachers, involvement in school activities, and providing an environment that supports child development at home. In addition, collaboration between parents and schools has proven effective in improving the quality of education and child development. This study concludes that parental involvement as educational partners plays a very important role in creating an optimal learning environment for early childhood.